Motivational Writing Problems of College Students in English Class - Naria Fitriani; Sabarniati Sabarniati (JETLi: Journal of English Teaching and Linguistics, 2021)
For college students, mastering foreign language such as English brings profitable for their career. Producing the language decently such as the ability of writing in English is one of the output in the language acquisition. In this study, non-English students in the end of their study were chosen as they’ve completed English courses. Moreover, the students were finishing their final project, definitely including the English abstract. Based on their learning experience, the writing process of English abstract showed indirectly their language ability. Regarding with, this study aims at finding whether the students have any learning progress during their study in the college. Additionally, not only the learners’ motivation but also their learning habit, their confidence, and the learning facility during learning English were questioned in this study. The students completing their final project at the certain time were interviewed towards their learning language habits particularly in writing. The data collected were transcribed, analyzed and interpreted qualitatively. The results show that 77.3% of the students felt they have more progress during the target language instruction. Furthermore, 50% of the students believe in stating English on text though they confessed they (68.2%) have lack of English practicing at home. The students’ positive attitudes presented due to their motivation in learning the language. The findings also indicated that all students (100%) believed that their teacher or lecturer motivates them to practicing writing English.